Status and Preliminary Research on Non-Synthetic Herbicides for Organic Production - James J. Ferguson; Carlene A. Chase (EDIS, 2005)
Procedures for identifying and registering non-synthetic herbicides for possible use in organic production are complex, involving federal and state laws and regulations as well as national and local organic certifying agencies. Our purpose is to explain this process and to review preliminary research on several non-synthetic herbicides. This document is HS1003, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: January 2005.